2023
DOI: 10.1186/s12905-022-02136-8
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the ovulatory cycle and its determinants among women of childbearing age in Haiti: a population-based study using the 2016/2017 Haitian Demographic Health Survey

Abstract: Background The knowledge of ovulatory cycle (KOC) is the base for natural family planning methods, yet few studies have paid attention to women’s KOC. This study aimed to assess the prevalence of correct KOC and its determinants among women of childbearing age in Haiti. Methods Data from the nationally representative cross-sectional Haiti Demographic and Health Survey 2016/17 were used. STATA/SE version 14 was employed to analyse the data by compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(61 reference statements)
1
5
0
Order By: Relevance
“…The findings revealed that the level of education of women was positively and expressively associated factors with KOC. Women with secondary education status were 24% more likely to have KOC (AOR: 1.24, 95% CI:1.006–1.528) compared to those with a primary level of education or no education, these findings align with previous studies [ 31 34 ]. Similarly, higher and secondary education level of husbands/partners were 2.5 times (AOR: 2.501, 95% CI:1.807–3.461) and 1.6 times (AOR: 1.599, 95% CI:1.305–1.959) more likely to contributes to women’s KOC respectively than no education.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The findings revealed that the level of education of women was positively and expressively associated factors with KOC. Women with secondary education status were 24% more likely to have KOC (AOR: 1.24, 95% CI:1.006–1.528) compared to those with a primary level of education or no education, these findings align with previous studies [ 31 34 ]. Similarly, higher and secondary education level of husbands/partners were 2.5 times (AOR: 2.501, 95% CI:1.807–3.461) and 1.6 times (AOR: 1.599, 95% CI:1.305–1.959) more likely to contributes to women’s KOC respectively than no education.…”
Section: Discussionsupporting
confidence: 89%
“…For our study, we categorized women into two groups according to KOC. Depending on the women’s responses, they were classified as ‘having accurate KOC’ who answered - were at “the middle of the menstrual cycle” and ‘not having accurate KOC’ refers to those who responded the fertile period was “during her period”, “after the period ended”, “before period begins”, “at any time”, “others” and “don’t know” [ 21 ].…”
Section: Variable Descriptionmentioning
confidence: 99%
See 3 more Smart Citations